Chromium removal from contaminated waters using nanomaterials – a review - Almeida , Joana C. (2019)
Current environmental policies aim to reduce the levels of toxic substances in aquatic ecosystems and to promote the water reuse after appropriate treatment of wastewater. Chromium is a hazard element present in effluents of various industries that should be reduced to achieve the objectives of those policies. Most of the results reported in the literature concern the use of nanomaterials for chromium sorption dissolved either in synthetic or mono-elemental spiked solutions. The present work reviews the results of research undertaken in the last decade on the application of various nanomaterials to decrease chromium concentrations in contaminated waters. Major factors influencing the removal efficiency were examined. Because most of the published studies are based on simple experiments with deionised water and mono contamination further studies are suggested focused on effects of natural and artificial chelators, interferences of other trace elements competing with chromium sorption, reduction the sorbent mass per water volume.